First transition series metal–organic frameworks: synthesis, properties and applications. Issue 22 (25th October 2021) - Kaushal, Sandeep; Kaur, Gurmeet; Kaur, Jasmeen; Singh, Prit Pal
Abstract : Metal organic frameworks (MOFs) have captured immense attention in the last decade, owing to their better adsorption properties as compared to those of organic as well as inorganic materials, like enormous surface area, highly porous nature, tunable pore size, and high stability. Abstract : Metal organic frameworks (MOFs) have captured immense attention in the last decade, owing to their better adsorption properties as compared to those of organic as well as inorganic materials, like enormous surface area, highly porous nature, tunable pore size, and high stability. Herein, the regular advancements in MOFs of metals of the first transition series, their morphology, properties, synthesis methods, and numerous applications like gas storage, separation, ion-exchange and catalysis have been discussed. The doping of MOFs and their composites has been classified and discussed, in addition to fabrication of MOFs with various types of organic linkers. MOFs have been discussed for their sustainable and convenient use in future. Various characterization techniques confirmed the rigid, porous and fine structure of MOFs.